Pengaruh Biaya Produksi dan Biaya Distribusi Terhadap Harga Jual Pada UKM Gendis Meubel - Muhammad Faiz Roy’an; Fatchur Rohman (Accounting Study Program, Faculty of Economics and Business, 2021)
One way to determine the selling price is to know the costs incurred to provide goods/services. Production costs are costs that need to be taken into account by the company to determine the selling price. Distribution costs are costs used by producers to distribute goods that have been produced to consumers, either in the form of transfer of rights to the transfer of ownership of an item. This study aims to analyze the effect of production costs and distribution costs on the selling price of SME Gendis Furniture. This research was conducted at UKM Gendis Furniture Jepara furniture. The data used in this study is secondary data obtained from the financial statements of SMEs Gendis Furniture. The sampling technique used is non-probability sampling. The data analysis method used is multiple linear regression analysis with the help of SPSS (Statistical Product and Service Solution) Version 20. Based on the results of the analysis, it shows that production costs have a positive and significant effect on selling prices. While distribution costs have no effect.